(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the techniques of synonymic and antonymic translation, two essential strategies used by translators to convey meaning across languages. Synonymic translation involves replacing a word or expression in the source language with a similar word in the target language, while antonymic translation uses the opposite of the original term to clarify meaning. Both methods are crucial in overcoming the limitations of direct translation, particularly when exact equivalents are unavailable or would sound unnatural in the target language. The article highlights the challenges and benefits of each technique, emphasizing the need for translators to consider context, cultural nuances, and the intended tone of the message. It also underscores the role of these strategies in promoting effective cross-cultural communication and adapting texts to fit the linguistic and cultural norms of the target language